Portrayal of Tradition and Culture in the Novel the Moon also Sets by Osi Ogbu. - Tusiimeruhanga, Brendah (Kabale University, 2024)
The Moon Also Sets by Osi Ogbu was a seminal work in postcolonial literature that delved into the complicated dynamics of tradition and culture in a transforming Nigerian society. Set against the background of postcolonial Nigeria, the novel explored the situations of cultural identity and the tensions between old and new ways of life. This study aimed at investigating the nuanced portrayal of tradition and culture in Ogbu's narrative, examining how these elements shaped individual and collective identities in the postcolonial context. Osi Ogbu, a distinguished Nigerian writer, has profoundly contributed to the literary landscape by drawing from the rich oral storytelling traditions of his homeland. His works especially The Moon Also Sets reflected the social and political upheavals of postcolonial Nigeria portraying the nation's struggle with the legacies of colonialism and the challenges of modernization. The novel captured the essence of Nigerian life with vivid detail, highlighting the resilience of its people. Despite its significance, there was a notable gap in the scholarly analysis of the portrayal of tradition and culture in The Moon Also Sets. Existing literature often overlooked at Ogbu's nuanced depiction of themes, focusing instead on more prominent works within the postcolonial canon. This study sought to address this gap by providing a comprehensive analysis of the novel. The objectives of this study included exploring how characters' experiences reflect tradition and culture, analyzing the settings that highlight these themes, and evaluating the narrative techniques employed by Ogbu. The research questions focused on Ogbu's depiction of traditional Nigerian culture, the conflicts between tradition and modernity.By examining The Moon Also Sets within its cultural context, this study contributed to postcolonial literature by highlighting the significance of tradition in shaping narratives of identity and resistance. It enriched our understanding of Nigerian cultural heritage and deepened our literary appreciation of Ogbu's work. This research not only enhanced the discourse on postcolonial identity formation but also preserved and celebrated the enduring cultural practices that defined the Nigerian society.